Kesejahteraan Psikologis Orang Tua melalui Tradisi Tedhak Siten - Eka Zakiyya Salsabila; Idham Nazarrudin (Assertive: Islamic Counseling Journal, 2025)
Tedhak siten is one of the Javanese traditions that is carried out when a child begins to learn to walk, typically when they are about seven or eight months old, as a form of parental gratitude for the child's development. This study aims to find out the psychological well-being of parents through the Tedhak Siten Tradition. The method used is qualitative research using a descriptive approach. This research also conducted interviews. The researcher interviewed parents about their psychological feelings regarding the Tedhak Siten Tradition. Tedhak Siten is one of the traditional Javanese rituals, or Slametan, observed during a birth event. Tedhak Siten is typically performed when the child is 7 months old and first begins to walk or take steps on the ground. This ceremony involves a procession of children climbing seven stairs made of materials such as sugarcane or bamboo, then walking on the ground or sand. This ritual symbolizes the child's first step in life, with the hope that they will grow strong, independent, and blessed. In addition, tedhak siten is also a form of parents' prayers so that children will achieve success and happiness in the future.   Tedhak siten salah satu tradisi Jawa yang dilakukan ketika seorang anak mulai belajar berjalan, biasanya saat berusia sekitar tujuh atau delapan bulan sebagai wujud Syukur orangtua atas perkembangan anak. Penelitian ini bertujuan untuk mengetahui kesejahteraan psikologis orang tua dengan melalui Tradisi Tedhak Siten. Metode yang digunakan adalah Metode Kualitatif dengan menggunakan jenis penelitian Deskriptif. penelitian ini juga melakukan wawancara. Peneliti mewawancai mengenai perasaan psikologis orang tua yang telah melaksanakan Tradisi Tedhak Siten. Tedhak Siten merupakan salah satu Tradisi atau Slametan adat jawa dalam peristiwa kelahiran. Tedhak Siten biasanya dilakukan ketika anak berumur 7 bulan dan pertama kali turun atau menginjak kaki ditanah. Upacara ini melibatkan prosesi anak menapaki tujuh tangga yang terbuat dari bahan seperti tebu atau bambu, kemudian berjalan di atas tanah atau pasir. Ritual ini melambangkan langkah awal anak dalam kehidupan, dengan harapan ia tumbuh kuat, mandiri, dan mendapat berkah. Selain itu, tedhak siten juga menjadi wujud doa orang tua agar anak kelak mencapai kesuksesan dan kebahagiaan.